9(x-1)6=3(x+9)12

Simple and best practice solution for 9(x-1)6=3(x+9)12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-1)6=3(x+9)12 equation:



9(x-1)6=3(x+9)12
We move all terms to the left:
9(x-1)6-(3(x+9)12)=0
We multiply parentheses
54x-(3(x+9)12)-54=0
We calculate terms in parentheses: -(3(x+9)12), so:
3(x+9)12
We multiply parentheses
36x+324
Back to the equation:
-(36x+324)
We get rid of parentheses
54x-36x-324-54=0
We add all the numbers together, and all the variables
18x-378=0
We move all terms containing x to the left, all other terms to the right
18x=378
x=378/18
x=21

See similar equations:

| 1.06(550+x)=2(212+2x*1.06) | | X*4-8x*2-9=0 | | 0=25+5.3t-4.9t^2 | | -8+u÷2=-20 | | 2x2=4 | | 2x-30=5x-120 | | -13+35=-2(x+4) | | 3(7+8x)=93 | | (550+J)x1.06=2(212+2Jx1.06) | | 11.4+.6x=9.9+.6x | | 102=6(3d+5) | | 22=5w+7 | | 20x-15=15x+5 | | 5(x=2)=-30 | | -25=5.3t-4.9t^2 | | X^2+5x+200=0 | | 6x-x=9 | | 5+1×10=a | | 22.5+3x=90 | | 3(x-1.8)=2+1x | | 3y+17-5y=12-(6y+3) | | -3=5x+4 | | (4x+8)=(7x-1) | | 5+10+8=2x-6 | | 5u+2u=18 | | 133-1+45x=23x | | 3(3-9y)+1=31 | | -w+219=279 | | (x+5)^=49 | | 7x-4(x-9)=18 | | 9-4x=-6×+23 | | 0.25x=2+0.05x |

Equations solver categories